UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETER DAUM MIMBA (Azadirachta indica A.Juss) SECARA KLT-BIOAUTOGRAFI TERHADAP BAKTERI Staphylococcus aureus Dan Pseudomonas aeruginosa - Rachmat Kosman (As-Syifaa Jurnal Farmasi, 2009)
Research of antimicrobial activity assay of mimba leaves (Azadirachta indica A.Juss) the pleminary research has been done by screening test several microbes such as Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus mutans, Bacillus subtilis, Pseudmonas aeruginosa, Salmonella thyposa, Escherchia coli, Vibrio sp and  Candida albicans, to the methanol, ether, and n-Butanol extract of mimba leaves (Azadirachta indica A.Juss) in consentration 1 mg/ml. The result showed that the ether extract inhibited bacterial growth actively of Staphylococcus aureus and Pseudomonas aeruginosa. Antimicrobe potency assessment on ether extract of mimba leaves (Azadirachta indica A.Juss) has done by liquid-liquid dilution methode to find out the MIC value in consentration 10 mg/ml; 5 mg/ml; 1 mg/ml; 0.5 mg/ml and 0.1 mg/ml respectively which continue on solidified medium ti find out the MLC to predict the compound group in other extract which antimicrobe activity it was done bioautography TLC. The best result has been obtained from separating compound by TLC methode which used mixed eluen n-Hexane : Ethyl Acetate (6:4). The result showed that MIC could not be determined due to the turbidity of test solution, whilw manimum MLC of ether extract of mimba leaves (Azadirachta indica A.Juss) 10 mg/ml toward Staphylococcus aureus nor Pseudomonas aeruginosa bacteria. Bioautography TLC test on Staphylococcus aureus and Pseudomonas aeruginosa showed that the compound group which predicted to impart the antimicrobe activity to the ether extract of mimba leaves (Azadirachta indica A.Juss) was alkaloid.Key words : Azadirachta indica, Bioautography TLC, antimicrobe